Monitoring the agri-food system in Myanmar: Agricultural urban wholesale markets – April 2021 - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
Prices of major agricultural products in the two major urban wholesale markets of Mandalay and Yangon were collected during the month of April 2021. Compared to prices from a year earlier in April 2020: - Wholesale prices of mostly domestically consumed agricultural products, e.g., potato, onions, chili, and mung bean, are significantly lower by between -22 and -48 percent, likely linked to reduced demand compared to a normal year. - Wholesale prices of agricultural products linked to export markets, e.g., maize and pigeon pea, have increased slightly from 2 to 11 percent, likely because of the stabilizing effects of limited international market access. - Wholesale prices of agricultural products that are imported, such as palm oil, have increased significantly likely due to the problems in the port. For example, palm oil prices were up by 66 percent in Yangon compared to a year earlier.